Managing for the long run : lessons in competitive advantage from great family businesses - Miller, Danny; Le Breton-Miller, Isabelle; Breton-Miller, Isabelle Le. (Boston, Mass. : Harvard Business School Press, 2005)
This book provide a comprehensive framework that explains how brand name, family-controlled companies manage to outperform and outlast their competitors through their intergenerational pursuit of excellence driven by the values, traditions, and identities of their highly committed and well-organied familial owners.
Introduction: in search of long term winners -- What distinguishes great family businesses? -- Four priorities of great family controlled businesses -- Brand builders -- Craftsmen -- Operators -- Innovators -- Deal makers -- When family controlled businesses stumble -- Managing for the long run.
Includes bibliographical references and index.
aug 28/05/13
Loans
Keywords: Family-owned business enterprises -- Management; Success in business